2012
DOI: 10.1371/journal.pone.0047047
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of a Multifunctional Alanine-Rich Peptide Analogue from Pleuronectes americanus

Abstract: Recently, defense peptides that are able to act against several targets have been characterized. The present work focuses on structural and functional evaluation of the peptide analogue Pa-MAP, previously isolated as an antifreeze peptide from Pleuronectes americanus. Pa-MAP showed activities against different targets such as tumoral cells in culture (CACO-2, MCF-7 and HCT-116), bacteria (Escherichia coli ATCC 8739 and Staphylococcus aureus ATCC 25923), viruses (HSV-1 and HSV-2) and fungi (Candida parapsilosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 82 publications
3
32
0
1
Order By: Relevance
“…In the in vitro assays, the peptide mirabamide H showed the best antiviral activity with an IC 50 value around 40 µM, followed by F and G, both with 65 µM, and mirabamide E with 120 µM [98]. Most recently, in a study carried out by Migliolo et al (2012), the peptide Pa-MAP 1, derived from the polar fish called Pleunorectus americanus, had its structural, physicochemical, and antimicrobial properties extensively studied and showed not only antibacterial and antifungal activity, but also anti-tumoral and finally antiviral activity against HSV-1 (94%) and -2 (97%) [99]. In later assays, it was found that Pa-MAP 1 has a virucidal mechanism of action, which means that this peptide possibly interacts with some viral surface glycoprotein [100].…”
Section: Avps Derived From Marine Organismsmentioning
confidence: 99%
“…In the in vitro assays, the peptide mirabamide H showed the best antiviral activity with an IC 50 value around 40 µM, followed by F and G, both with 65 µM, and mirabamide E with 120 µM [98]. Most recently, in a study carried out by Migliolo et al (2012), the peptide Pa-MAP 1, derived from the polar fish called Pleunorectus americanus, had its structural, physicochemical, and antimicrobial properties extensively studied and showed not only antibacterial and antifungal activity, but also anti-tumoral and finally antiviral activity against HSV-1 (94%) and -2 (97%) [99]. In later assays, it was found that Pa-MAP 1 has a virucidal mechanism of action, which means that this peptide possibly interacts with some viral surface glycoprotein [100].…”
Section: Avps Derived From Marine Organismsmentioning
confidence: 99%
“…The promiscuous antifreeze Pa-MAP peptide, which consists of an α-helix composed of 11 amino acid residues, was isolated from the polar fish Pleuronectes americanus ( Table 2). The Pa-MAP exerted antimicrobial activity against bacteria, fungi, neoplastic cells, and also interacted with the viral envelope of the HSV types 1 and 2, inhibiting the infection of susceptible cells [77,[90][91][92].…”
Section: Peptides From Marine Organismsmentioning
confidence: 99%
“…One example is the promiscuous peptide Pa-MAP isolated from the fish Pleuronectes americanus , which beyond having shown broad antimicrobial activity against bacteria ( E. coli and S. aureus ), fungi ( Candida parapsilosis, Trichophyton mentagrophytes, and Trichophyton rubrum ) and tumor cells in culture (CACO-2, MCF-7, and HCT-116), also has activity against viruses (HSV-1 and HSV-2). The antiviral mechanism of this peptide has been suggested to involve its interaction with the viral envelope (Migliolo et al, 2012; Teixeira et al, 2013). …”
Section: Introductionmentioning
confidence: 99%